Penerapan Metode TOPSIS Untuk Merekomendasikan Pemilihan Jurusan Dalam Sistem Penerimaan Peserta Didik Baru (PPDB) Online Di SMK YAPPIKA Legok - Eltri Jumiarti; Joko Suwarno (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract YAPPIKA Legok Vocational School is one of the vocational high schools in Legok sub-district which annually holds New Student Admissions (PPDB). However, the process that is carried out is still manual, while nowadays it has been digitized. Besides that, prospective students experience problems in choosing majors that match their interests and talents. To overcome this, so that the New Student Admission (PPDB) process can be carried out online and able to provide recommendations or suggestions for prospective students in selecting majors that are in accordance with their interests and talents, the Technique for Order Preference By Similiarity to Ideal Solution (TOPSIS) method is used. . In the calculation process using data sources obtained from answers to questions that exist in the system. In the implementation of these methods to create applications using the PHP programming language and data storage using MySQL. The New Student Admission System (PPDB) with the Technique for Order Preference By Simiarity to Ideal Solution (TOPSIS) method will produce a test result form that states the prospective student has passed or not passed along with recommendations or suggestions of majors that the prospective participants should choose. Keywords: Prospective Students, System, PPDB, TOPSIS